The New Way of Beauty Experience from Korean Wave as Vocational Guidance in Indonesia - Nurbayani, Siti; Annuraini, A. (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2017)
Korean Wave called Hallyu is the most phenomenal global culture that spread around the world as well as Indonesia. Along with Hallyu syndrome, plastic surgery began to be known by the Korean fans in Indonesia. Participation of the media, in particular, information technology became an important key by the Korean wave invasion. Korean idol who is so pretty and charming make Korean fans want to emulate his idol. This study aims to discuss how the views of Indonesian young women within decision making undergo plastic surgery in beauty experience as the effect of the Korean wave invasion. Data were collected using a qualitative method by face-to-face interviews. Purposive sampling will be used for election respondent to Indonesian young women as Korean fans. The findings from this study show that Indonesian young women wish to have a face and body like a Korean idol. However, they did not even think to undergo plastic surgery. Culture, religious, and social expectations are the reason they do not undergo plastic surgery. They prefer to empower themselves through cosmetic skills in make-up and exercising. And it is used as a vocational guidance especially in beauty experience.